IMPLEMENTASI ARDUINO SEBAGAI SISTEM PENGENDALI OTOMATIS PADA MESIN PENGERING IKAN UNTUK MENINGKATKAN EFISIENSI DAN KUALITAS PRODUK - Suharman, Adelia; Arifin, Zaenal (SIGMA TEKNIKA, 2024)
Solar power or solar cell is one of the alternative energy sources that can be developed in Indonesia. Solar cell light detector is a new innovation designed specifically to automate the operation of the solar panels and to optimize the generation of electrical energy. The use of solar cell is expected to be more efficient and effective in the use of electrical energy in order to promote environmentally green technology. Hardware design consists of solar cell as a means of energy conversion of light energy into electricity were, the voltage level sensor, processor of data in the form of Arduino Uno, LCD monitor, servo motor, LDR sensors, batteries, and relay drivers. Based on the test results and the performance of the device, the system works as expected. when the battery voltage reaches the minimum voltage level sensor will detected presence of light, then the servo motor will moved the surface of solar panel towards the highest light intensity and battery charging process starts until it reaches the maximum limit that next recharging will stop filling and detect light.